The Challenge of Recurrent Bacterial Vaginosis and The Promise of Liposomal Probiotic - Arnova Reswari; Delima Istio Prawiradhani Putri (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Bacterial vaginosis (BV) is a common vaginal dysbiosis marked by the overgrowth of anaerobic bacteria and reduced Lactobacillus dominance. Despite antibiotic treatments, recurrence rates exceed 50% due to biofilm resistance and failed microbiota restoration. This narrative review describes that probiotics show promise but face challenges in colonization and stability. This review followed PRISMA guidelines, it screened 1,098 PubMed and Scopus studies (2015–2025). The studies used MeSH (Medical Subject Heading) terms like "Nanoparticle Drug Delivery," "Probiotics," and "Liposomes."Liposomal encapsulation improved probiotic viability (92% in 3D scaffolds) and vaginal colonization (79% for L. crispatus). Biofilm penetration increased by 60µm using cationic lipids, while recurrence rates dropped by 50% with liposomal probiotics versus placebo. Optimal formulations included DPPC:Chol (7:3) blends and pH-sensitive lipids for targeted release. Dual-action liposomes (probiotics + antibiotics) showed synergistic effects.Liposomal probiotics enhance BV treatment by protecting probiotics, disrupting biofilms, and reducing recurrence. Challenges remain in scalability and long-term safety